نابالغ افراد کی سوشل میڈیا سے وابستگی اور معاشرہ پر اُن کے منفی اثرات : The Engagement of Minors with Social Media and Its Negative Impacts on Society. - Khan, Naimat Ullah (MEI, 2025)
This study presents a critical analysis of the engagement of minors with social media and its adverse effects. In contemporary times, modern facilities such as mobile phones and the internet have become an integral part of daily life; however, their misuse and untrained utilization are proving highly detrimental for both family and society. Social media has contributed to the erosion of modesty among the younger generation, the promotion of music and dance, the normalization of immodest dress codes, the prevalence of falsehood, and the diminishing distinction between lawful and unlawful social boundaries. Similarly, the negative influence of visual media, including images and dramas, is distorting the mindset of children and undermining social and moral values. The findings suggest that it is the responsibility of parents to nurture their children in accordance with Islamic principles and to educate them about both the constructive and destructive aspects of modern technologies, thereby fostering the development of a balanced and virtuous society.